Core loss estimation under sinusoidal and non-sinusoidal flux density waveforms overview and challenges - Melo , Pedro Miguel Azevedo de Sousa (Neutro à Terra, 2021)
Nowadays, electrical machines design and control developments are much attached to simulation models. Accurate loss estimation methods are fundamental for improving efficiency, but also to achieve the desired operation conditions